Assembly Challenge: a robot competition of the Industrial Robotics Category, World Robot Summit – summary of the pre-competition in 2018. (2nd September 2019) - Yokokohji, Yasuyoshi; Kawai, Yoshihiro; Shibata, Mizuho; Aiyama, Yasumichi; Kotosaka, Shinya; Uemura, Wataru; Noda, Akio; Dobashi, Hiroki; Sakaguchi, Takeshi; Yokoi, Kazuhito
ABSTRACT: The World Robot Summit (WRS) is a robotic 'challenge and exposition' organized by the Japanese government to accelerate social implementation, research and development of robots working in realistic daily life, society, and industrial fields. In this paper, we introduce a robot competition of the Industrial Robotics Category of the WRS, called 'Assembly Challenge', which is organized by the WRS Industrial Robotics Competition Committee in order to promote the development of the next-generation production systems that can respond to new production demands in agile and lean manners. Prior to the main competition in 2020, a pre-competition was held in 2018 with 16 participating teams from around the world. In this paper, we introduce the contents and results of this pre-competition, analyze the results, and give a perspective for the 2020 main competition. GRAPHICAL ABSTRACT: